Isolasi Streoid Dari Fraksi Etil Asetat Hedyotis Philippensis (Jurnal Pilar Sains, 2003)
Chemical constituent has been isolated from the dry acrial parts of Hedyotis philippensis. The finely choppedmaterial was bextracted with methanol then fractionated into different polarity of solvent; hexane, ethilacetate and buthanol. Needled colorless (Melting point 140-1420C) has been isolated from Ethil acetatefraction and based on its spectroscopic data particularly IR (Infra red) and ‘H-NMR (Proton of NuclearMagnetic Resonantion), it is identified as stigmasterol.